Developmental Coordination Disorder Affects the Processing of Action-Related Verbs - Mirabella, Giovanni; Del Signore, Sara; Lakens, Daniel; Averna, Roberto; Penge, Roberta; Capozzi, Flavia (Frontiers in Human Neuroscience, 2017)
Processing action-language affects the planning and execution of motor acts, which suggests that the motor system might be involved in action-language understanding. However, this claim is hotly debated. For the first time, we compared the processing of action-verbs in children with Developmental Coordination Disorder (DCD), a disease that specifically affects the motor system, with children with a typical development (TD). We administered two versions of a go/no-go task in which verbs expressing either hand, foot or abstract actions were presented. We found that only when the semantic content of a verb has to be retrieved, TD children showed an increase in reaction times if the verb involved the same effector used to give the response. In contrast, DCD patients did not show any difference between verb categories irrespective of the task. These findings suggest that the pathological functioning of the motor system in individuals with DCD also affects language processing.